IMPROVING STUDENTS’ MOTIVATION IN SPEAKING ABILITY BY USING STORY RETELLING - Kusdianang, Pamujo Effa; Linggar Bharati, Dwi Anggani (English Education Journal, 2016)
This study investigated story retelling in relation to students’ motivation in speaking ability of narrative story. The objectives of the study were to find out: (1) Problems faced by the students of the grade XI of SMA N Jatitujuh in teaching learning process of speaking, (2) How story retelling was implemented in speaking class, (3) How story retelling improved students’ speaking ability in speaking class, (4) How story retelling improved students’ motivation in speaking class. The design of this research was three cycles of Classroom Action Research. The participants of the research were 30 students of eleventh graders of SMAN Jatitujuh, Majalengka. The study used questionnaire, observation and test as the instruments. The data of the research were collected through questionnaire, observation and test. The results of the study were firstly, the students got bored and tended to be passive, they were lack of grammar, vocabularies, fluency and correct pronunciation. Secondly, story retelling was implemented by using group discussion, students experienced to retell the story both in group and in front of the class. Thirdly, the result of students’ speaking skill showed some improvements as follows; from pre-cycle to cycle 1 increased 6%. From cycle 1 to cycle 2 increased 9.92 % and from cycle 2 to cycle 3 increased 7.31 %. Fourthly, based on the observation, the students who have high motivation increase from 37% in the pre-cycle to 40 % in the first cycle then become 70 % in cycle 2 and finally 90 % in cycle 3. The result of students’ motivation based on the questionnaire from pre-cycle to cycle 1 increased 9.29 %. From cycle 1 to cycle 2 increased 10.97% and from cycle 2 to cycle 3 increased 4.74%. Based on the findings, story retelling could improve students’ motivation in speaking ability of the second semester students of SMAN Jatitujuh Majalengka academic year 2014/2015.